2018
DOI: 10.1021/acs.energyfuels.8b01683
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Lacustrine Shale Reservoir and Its Effect on Methane Adsorption Capacity in Fuxin Basin

Abstract: The Lower Cretaceous Shahai and Jiufotang Formation in Fuxin Basin, located northwest of Liaoning Province, with stable planar distribution contains abundant shale gas reserves, which are key horizons in the exploration breakthrough of the Mesozoic continental shale gas in northeastern China. FuYe-1 (FY-1) well was recently drilled, and it is an important shale gas parameter well in the Fuxin Basin area. A total of 60 shale samples were collected from Shahai and Jiufotang Formation of FuYe-1 well and DY-1 well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Without exception, the fan delta deposits in the whole basin were considered to be broadly developed on the western gentle slope and eastern steep slope (Cai et al., 2011; Chen et al., 2019; Li et al., 1985; Xu et al., 2020), due to the lack of integrally visual sedimentary stratigraphic evidences in different locations. However, we recognize a series of widespread subaqueous gravity flow deposits from K 1 jf to K 1 sh in the central‐eastern part of the basin from the recent borehole and seismic data (Figures 3–5), which have not been previously reported in the Fuxin Basin (Chen et al., 2018, 2019).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Without exception, the fan delta deposits in the whole basin were considered to be broadly developed on the western gentle slope and eastern steep slope (Cai et al., 2011; Chen et al., 2019; Li et al., 1985; Xu et al., 2020), due to the lack of integrally visual sedimentary stratigraphic evidences in different locations. However, we recognize a series of widespread subaqueous gravity flow deposits from K 1 jf to K 1 sh in the central‐eastern part of the basin from the recent borehole and seismic data (Figures 3–5), which have not been previously reported in the Fuxin Basin (Chen et al., 2018, 2019).…”
Section: Discussionsupporting
confidence: 50%
“…This study established a new evolution model of sedimentary facies during the whole early Cretaceous deposition in the Fuxin Basin (Figure 5). Although such models have been reported in a series of early Cretaceous half‐graben basins (NE China) (J. Jia et al., 2014; Yin et al., 2008), widely developed subaqueous fans in the eastern Fuxin Basin have never been demonstrated (Chen et al., 2018, 2019). We reveal the development of two depositional systems, a fan delta–slump fan–shore‐shallow lake and a subaqueous fan–semi‐deep lake (Figures 5 and 8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that mudstones of the Shahai Formation were mainly composed of clay minerals, quartz, feldspar and carbonate minerals, with pyrite present in small amounts or absent. Identified clay minerals include mixed-layer illite-smectite, illite, chlorite and little kaolinite (Chen et al 2018;Kang et al 2019). Mudstones contain abundant chemical weathering products derived from their source rocks, allowing the chemical weathering history in the source area to be revealed (Garzanti et al 2013).…”
Section: Materials and Analytical Methodsmentioning
confidence: 99%